Relationship between sublingual varices and hypertension: a systematic review and meta-analysis - Hosein Eslami; Fatemeh Halimi Milani; Fatemeh Salehnia; Negar Kourehpaz; Katayoun Katebi (BMC, 2024)
Abstract Background Previous research has investigated the connection between sublingual varices (SV) and cardiovascular disease, aging, and smoking. However, it is still unclear whether arterial hypertension affects the presence of SV. This meta-analysis aimed to investigate the relationship between hypertension and the presence of SV. Methods The literature search was performed using PubMed, Web of Science, Scopus, Google Scholar, and Embase for cross-sectional studies until July 2023. PRISMA guidelines were used for article selection. A meta-analysis using standardized mean differences by a random effects model was conducted to pool studies. Results A total of 568 articles were retrieved, of which twelve were included in the meta-analysis. Cumulatively, 2543 samples in the case group (1185 with hypertension) and 3897 samples (821 with hypertension) were studied in the control group. Using the random effects model, the pooled odds ratio (OR) revealed a significant association between hypertension and sublingual varices (OR = 2.66; 95% CI: 1.69-4.18). Conclusion The meta-analysis showed a significant and positive association between sublingual varices and hypertension. SV's presence could be used by dentists as a non-invasive indicator of hypertension screening.